ANALISIS PUTUSAN NOMOR 1214/PDT.G/2023/PA.SRG. GUGATAN HAK ASUH ANAK YANG JATUH ANAK PADA SUAMI - Prasetyo S., Pukka Dean; Wahyuni, Friska; Wulandari, Ayu; Fatimahtuzzahro; Murofikoh, Dede Ika (COMMUNITY OF RESEARCH LABORATORY (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN), 2025)
Divorce is a legal event that not only completes the marital relationship, but also has major consequences for children, especially in terms of determining who has the right to take care of them. Generally, in accordance with Article 105 letter (a) of the Compilation of Islamic Law (KHI), custody of children who have not yet mumayyiz is held by the mother. However, this rule is not absolute and must still take into account the best principles for the child. This study aims to analyze the division of custody of minors to fathers after divorce and explore legal considerations from the Panel of Judges in Decision Number 1214/Pdt. G/2023/PA. Srg who decides custody is given to the father. This study conducts a juridical-normative research method with an approach to laws and regulations, conceptual, and case studies. Data was collected through a literature review on regulations, a compilation of Islamic Law, and an analysis of court decisions. The findings of this study show that custody can be given to fathers if there is strong evidence that the mother is unable to carry out responsibilities in parenting, both physically, morally, emotionally, and economically. In this situation, the Board of Judges evaluated that the mother's living conditions were inadequate, there was neglect in parenting because children were often left to elderly grandmothers, and lack of attention due to a new marriage. Meanwhile, fathers are proven to have better housing stability, financial support, and parenting commitments. The Board of Judges makes decisions based on the principles of maslahah, the best interests of the child, and alignment with Article 3 of the Convention on the Rights of the Child.